A new teaching concept on quantum physics in secondary schools - Bitzenbauer, Philipp; Meyn, Jan-Peter (Physics Education, 2020)
In this article, an approach to integrate contemporary quantum physics into secondary school teaching is presented. The Erlanger concept on quantum optics provides an experimental-based guideway to aspects of modern quantum physics. We avoid the traditional historical approach in order to overcome the lack of modern concepts of quantum physics. In an acceptance survey, initial empirical evidence for the acceptance of the developed explanatory approaches was evaluated.
Keywords: quantum optics; anticorrelation factor; single Photons; acceptance survey